Characteristics of cognitive and psychoemotional disorders in chronic cerebral ischemia - Madjidova Yo.N; Nizamkhodzhaeva Sh (Genius Journals, 2023)
Chronic cerebral ischemia is a slowly progressive brain lesion caused by chronic cerebrovascular insufficiency. Manifested by a complex of cognitive, emotional and motor disorders . CCI is one of the main causes of disability in old age. This article considers cognitive and psycho-emotional disorders in chronic cerebral ischemia.
Keywords: Chronic ischemia of the brain; cognitive sphere